ภาพแทนผู้หญิงมุสลิมกับความเหยื่อในนวนิยายเรื่อง รุสนี ของมนตรี ศรียงค์ - มีนา, นารีดา; ปฤชากุล, วิมลมาศ (Al-HIKMAH Journal, 2019)
Abstract This study entitled “The Representation of Muslim Women and Victimization in the Novel of Rusnee Written by Montri Sriyong”, which was produced after the violent events in the southernmost provinces in the period of 2004, aims to investigate the representation of Muslim women and victimization. The findings show that the representation can be divided into two points: the Muslim women and victims of the situational unrest and the Muslim women and victims of the sexual violence. The representation of Muslim women presented through the novel is the image of women assaulted by the violence causing them to be the victims of both situational violence and sexual abuse being assaulted by men both insiders and outsiders. As a result, the representation of the Muslim women portrays loss, weakness, sadness, depression, aimlessness and need to be protected by the men bringing them going through those tough situations. The representation of Muslim women shaped by Montri Sriyong, who was a Buddhist author, reveals that it is to extend understanding towards situational violence in the southernmost provinces and attempt to adapt outsiders’ attitudes to the people in the area acquiring news and information of the continuous unrest situation for ages. This leads to a stereotypes of the outsiders that all people in the area get involved with the terrorists resulting in the stereotype of negative mindsets of hatred towards Muslims and discrimination in Thai society. The author of this novel selected females as the characters presenting violence in the area that affects both Muslims and Buddhists being victimized inevitably.